2012
DOI: 10.17221/5914-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Biologically active substances from water invertebrates: a review

Abstract: Some species of invertebrates especially bryozoans (Bryozoa syn. Ectoprocta) and marine sponges (Porifera) are very important sources of pharmacologically exploitable compounds. These substances are probably produced to protect themselves from fish predators and may be an advantage in competition. The real sources of compounds with these antipredatory effects are probably not marine invertebrates themselves, but microscopic symbionts or food which they feed on. Bryostatins from bryozoan species Bugula neritina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 49 publications
(97 reference statements)
0
9
0
Order By: Relevance
“…Tunicates are also potential antiviral (Murti and Agrawal, 2010), anticancer (Shaala and Youssef, 2015), inhibitor and induces apoptosis of breast (MCF-7; MDA-MB) cancer cells and also used for phase II cancer treatment (Zelek et al 2006;Michaelson et al 2012;Atmaca et al 2013), as inhibitor of breast cancer cells by JNK dependent apoptosis (Gonzalez-Santiago et al 2006), breast and prostate cancer (Kalimuthu et al 2014). One of the bioactive compounds produced by tunicate is used to cure refractory soft-tissue sarcomas (Sinko et al 2012). Sangkarang Archipelago which was previously known as Spermonde is located South West off Makassar, consisting more than a hundred islands.…”
Section: Introductionmentioning
confidence: 99%
“…Tunicates are also potential antiviral (Murti and Agrawal, 2010), anticancer (Shaala and Youssef, 2015), inhibitor and induces apoptosis of breast (MCF-7; MDA-MB) cancer cells and also used for phase II cancer treatment (Zelek et al 2006;Michaelson et al 2012;Atmaca et al 2013), as inhibitor of breast cancer cells by JNK dependent apoptosis (Gonzalez-Santiago et al 2006), breast and prostate cancer (Kalimuthu et al 2014). One of the bioactive compounds produced by tunicate is used to cure refractory soft-tissue sarcomas (Sinko et al 2012). Sangkarang Archipelago which was previously known as Spermonde is located South West off Makassar, consisting more than a hundred islands.…”
Section: Introductionmentioning
confidence: 99%
“…Already in the 1950s it was discovered that sponges yield a wide array of biologically active secondary metabolites [ 1 ]. Since then more than 5300 chemical compounds have been described in sponges [ 2 ]. Marine natural products research has been driven mainly by pharmacological screening programs, which aim at the discovery of new chemical structures with pharmacological activity, neglecting the ecological functions of these compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies concerning the bioactivity of sponges have been conducted, extending explorations to the extraction and isolation of secondary metabolites. Bioactive substances from sponges or associated microorganisms have shown broad spectrum properties such as anticancer, antibacterial, antifungal, antiviral, antiprotozoal, anthelmintic, anti-inflammatory, immunosuppressive, neurosuppressive and antifouling [19]. It is suggested that (at least) some of the bioactive secondary metabolites isolated from sponges are produced by functional enzyme clusters, which originated from the sponges and their associated microorganisms [15].…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…These secondary metabolites are now used as suppressants in numerous diseases worldwide. In the study of Sinko et al [19], it was clearly stated that the natural products from wreath lichen (Cryptotheca) served as a template for the synthesis of the anti-viral drug Ara-A that led to the development of the medicinal drug for AIDS. Although these are terrestrial species, it has been stated that there has been a remarkable similarity between compounds produced by organisms in land and on water and should therefore put forward that secondary metabolites isolated from both areas have equally great potential for medical uses.…”
Section: Review Of Related Literaturementioning
confidence: 99%